Factors Associated with Helping Behavior When Witnessing an Accident: A Cross-sectional Survey (International Journal of First Aid Education)
Background: First aid is the immediate help provided to the ill or injured. Although it can be lifesaving, many people refrain from helping when encountering a person in need. This study aimed to describe the types of accidents people are most likely to encounter in daily life and to assess the association between several variables, including having received first aid training and helping behavior.Methods: An online survey was distributed from December 2016 to February 2017. The factors affecting provision of first aid and calling of emergency services were analyzed using multivariable logistic regression.Results: More than half of the 59,477 respondents (51.9%) stated that they had encountered an accident in the past five years. A total of 59,110 accidents were reported. First aid was provided in 70.2% of accidents and emergency services were called in 72.0% of accidents. Age, gender, WHO region, type of accident and environment of the accident were all significantly associated with providing first aid and calling emergency services. People who were trained in first aid were more likely to provide first aid or to call for emergency services than untrained people (p<0.0001).Conclusion: Several factors were associated with helping behavior, including but not limited to having received first aid training. There is a need for lifelong training, with special attention to those subgroups that are less likely to report helping behavior.